Bibliometrics The Relationship between OBSE (Organization-Based Self-Esteem) and Sustainability in HR - Judijanto, Loso; Malik, Abdul Hadi (West Science Social and Humanities Studies, 2025)
This study offers a bibliometric examination of the correlation between Organization-Based Self-Esteem (OBSE) and sustainability in human resource management (HRM), utilizing data from the Scopus database spanning 2000 to 2025. The study utilizes VOSviewer and Bibliometrix software to delineate publishing trends, authorship networks, keyword co-occurrences, and topic evolution, thereby identifying intellectual tendencies and research deficiencies. Findings reveal that "sustainability," "green HRM," and "employee engagement" are prevalent study themes, highlighting the increasing incorporation of human-centered methodologies in sustainability research. Collaboration maps identify Asia—specifically India and Malaysia—as prominent research centers, linking with Europe and the United States within global networks. The results highlight OBSE as a psychological mechanism that connects employee self-esteem to sustainable performance and creativity in enterprises. Theoretically, the research expands the micro-foundations of sustainable human resource management, while practically, it emphasizes the significance of esteem-driven engagement in attaining organizational sustainability. Limitations and avenues for future research are examined.